PERAN CONCEPT ART DALAM PEMBUATAN PROYEK FILM ANIMASI BATIK GIRL - FICUSIA - Ramadhan, Rangga Syahputra (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2022)
Currently, the number of drug users is increasing every year. This problem is not only faced by Indonesian people, but also almost all countries. From the statement of the National Narcotics Agency (BNN), there were 851 cases of drug abuse involving a total of 1350 suspects in 2022. And the data increased from the previous year. Many people already know that drugs are prohibited items that are very dangerous because they not only harm the users themselves, but also the people around them because they can cause symptoms such as dependence, hallucinations and convulsions. It is therefore very important to remind relatives or friends to avoid drugs because if they use drugs, they have to deal with the law and can be imprisoned for a long time. Based on this problem, Yayasan Cinderella Indonesia worked with the police to give jobs to female prisoners where the proceeds would be donated to people in need. The foundation then came up with the idea to create an animation project to inform the public about the dangers of drugs. And in 2021, Cinderella Foundation collaborated with Politeknik Negeri Batam in creating an animated film project entitled Ficusia.